2010
DOI: 10.1063/1.3474964
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectric response of ferroelectric nanowires: Size effect and electric energy harvesting

Abstract: The size effect on pyroelectric response of ferroelectric nanowires and nanotubes is analyzed. The pyroelectric coefficient strongly increases with the wire radius decrease and diverges at critical radius R cr corresponding to the size-driven transition into paraelectric phase. Size-driven enhancement of pyroelectric coupling leads to the giant pyroelectric current and voltage generation by the polarized ferroelectric nanoparticles in response to the temperature fluctuation. The maximum efficiency of the pyroe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 24 publications
0
53
0
Order By: Relevance
“…Theoretical approaches based on thermodynamic, electrostatic, and statistical mechanics considerations have been used to understand the adiabatic temperature changes in polar solids 38 and asymmetric ferroelectric tunnel junctions, 80 as well as pyroelectric response of ferroelectric nanowires. 81 Although phase-field models have been developed for a number of materials systems that include ferroics and multiferroics, 82 only limited studies have considered their application to understand correlations between microstructural features and electrothermal properties. 83 In terms of atomistic approaches, there exist several methodologies based on first principles coupled with nonequilibrium molecular dynamics.…”
Section: Device and System Considerations For Materials Selection Andmentioning
confidence: 99%
“…Theoretical approaches based on thermodynamic, electrostatic, and statistical mechanics considerations have been used to understand the adiabatic temperature changes in polar solids 38 and asymmetric ferroelectric tunnel junctions, 80 as well as pyroelectric response of ferroelectric nanowires. 81 Although phase-field models have been developed for a number of materials systems that include ferroics and multiferroics, 82 only limited studies have considered their application to understand correlations between microstructural features and electrothermal properties. 83 In terms of atomistic approaches, there exist several methodologies based on first principles coupled with nonequilibrium molecular dynamics.…”
Section: Device and System Considerations For Materials Selection Andmentioning
confidence: 99%
“…Recent studies include attempts at energy conversion using bulk crystals of relaxor materials 15 and ferroelectric nanowires. 16 Since most practical applications utilize "thick" ferroelectric films (generally in excess of 200 nm), it is important to understand pyroelectricity in these systems and explore new mechanisms for improving the pyroelectric coefficient. Epitaxial ferroelectric thin films which possess ferroelectric properties that are tunable with strain, composition, and temperature offer an exciting potential for such a study, but a comprehensive theoretical understanding is currently unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of larger particles may interfere with the homogeneity of the liquid crystal, and thus destroy the orientation of the LC molecules, while the smaller particles lose their ferroelectric properties [7]. Previous work [9,10,[13][14][15][16] has shown that the preparation of ferroelectric nanoparticles is a difficult process. In recent years, one found new processes for the production of BaTiO 3 ferroelectric nanoparticles, including sol-gel method, hydrothermal method, molten salt method, mechanochemical synthesis or combustion synthesis [17,18].…”
Section: Methodsmentioning
confidence: 99%